2008
DOI: 10.1002/j.2050-0416.2008.tb00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of High Cell Density Fermentations with Different Lager Yeast Strains

Abstract: To improve the productivity of the beer fermentation process, several strategies can be adopted. One of these promising strategies could be the increase of suspended yeast cells in the reactor. Therefore, the fermentation characteristics of 11 lager yeast strains were studied in normal pitched worts (20 × 10 6 cells/ mL) (LD) and in worts with a four-fold higher pitching rate (HD). The fermentation rate was 2-4 times increased when high initial cell levels were used. The net yeast growth was somewhat similar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
4
25
0
3
Order By: Relevance
“…These results share similarity with a previous report [70]. On the contrary, Verbelen et al [80] reported that the inXuence of pitching rate on aroma compound production was rather limited, with the exception of total diacetyl levels, which strongly increased with the pitching rate.…”
Section: Yeast Pitching Ratesupporting
confidence: 86%
“…These results share similarity with a previous report [70]. On the contrary, Verbelen et al [80] reported that the inXuence of pitching rate on aroma compound production was rather limited, with the exception of total diacetyl levels, which strongly increased with the pitching rate.…”
Section: Yeast Pitching Ratesupporting
confidence: 86%
“…Similar concentrations were detected by Verbelen et al (2009a) in beer. Other authors showed that ester levels were negatively influenced by higher pitching rates (Verbelen et al, 2008). A similar result was observed in this study for isoamyl acetate and 2-phenylethyl acetate, compounds with fruity and flowery flavours, respectively.…”
Section: Effect Of Pitching Rate On Mead Aroma Profilesupporting
confidence: 77%
“…No differences in 3-methyl-1-butanol were observed in meads fermented at different pitching rates by the strain ICV D47, whereas a higher concentration of this alcohol was detected only at the lowest pitching rate (1.5 Â 10 5 CFUs/mL) with the strain QA23. Different results were obtained by Mateo et al (2001), Erten et al (2006), Verbelen et al (2008) and Verbelen et al (2009a), who indicated a direct dependence of the concentration of that compound on inoculum size. Esters represented the most diverse group with ten compounds quantified.…”
Section: Effect Of Pitching Rate On Mead Aroma Profilementioning
confidence: 92%
“…However, the levels of aroma compounds, especially esters, in beer vary with fermentation temperature (20,30). Increasing the yeast inoculum also alters the aroma profile and increases fermentation rate but only up to a limit (22,28,29).…”
mentioning
confidence: 99%